Apocalypse on the Mount - Kusio, Mateusz (The Biblical Annals, 2021)
This article claims that the “passing away of heaven and earth” (Matt 5:18), until which the Torah is to be preserved whole according to Matthew, is proleptically realised during the crucifixion which is accompanied by the darkening of the sun (27:45) and earthquake (27:51b). Consequently, at that point the Torah ceases to be the central and unique legal code for Matthew and becomes mediated by Jesus’ own teaching. This claim is evidenced by Matthew’s subtle, yet sudden disinterest with the Law after the crucifixion.